Play and learning a discussion with Barbara Biber [videorecording] - Biber, Barbara; National Association for the Education of Young Children (Washington, D.C. National Association for the Education of Young Children, 1985)
Barbara Biber discusses why play is important for young children and how teachers can explain the value of play for children's learning.
Keywords: Education, Preschool; Play